Some New Inequalities for the Strictly Monotonic Functions and Positive n-Tuples
In this paper we give the generalization of the inequalities equation* split &n^n_i=1a_i^n ≥ ^n_i=1a_i^t ^n_i=1a_i^n-t ≥ ^n_i=1a_i^s ^n_i=1a_i^n-s ≥ (^n_i=1a_i^n2)^2 , & 0 < t < s < n2, a_i>0,i {1,…,n\